Seiberg-Witten-Like Equations Without Self-Duality on Odd Dimensional Manifolds (Journal of Partial Differential Equations, 2020)
In this paper, Seiberg-Witten-like equations without self-duality are definedon any smooth 2n+1-dimensional Spinc manifolds. Then, a non-trivial solution isgiven on the strictly-Pseudoconvex CR-5 manifolds endowed with a canonical Spinc-structure by using Dirac operator associated with the generalized Tanaka-Webster connection. Finally, some bounds are given to them on the 5-dimensional Riemannianmanifolds.